2008
DOI: 10.1111/j.1526-100x.2008.00357.x
|View full text |Cite
|
Sign up to set email alerts
|

Tamarix as Habitat for Birds: Implications for Riparian Restoration in the Southwestern United States

Abstract: Exotic vegetation has become a major habitat component in many ecosystems around the world, sometimes dramatically changing the vegetation community structure and composition. In the southwestern United States, riparian ecosystems are undergoing major changes in part due to the establishment and spread of the exotic Tamarix (saltcedar, tamarisk). There are concerns about the suitability of Tamarix as habitat for birds. Although Tamarix habitats tend to support fewer species and individuals than native habitats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
139
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(142 citation statements)
references
References 39 publications
3
139
0
Order By: Relevance
“…Because of this conflict, salt cedar eradication has been delayed while other control strategies are devised (U.S. Fish and Wildlife Service 1997). Without restoration efforts that assure the re-establishment of native riparian vegetation and restoration of ecosystem function, the removal of invasive salt cedar will result in a loss of nesting habitat for the endangered flycatcher (Zavaleta et al 2001, Dudley and DeLoach 2004, Sogge et al 2008, Dudley and Bean 2012.…”
Section: Discussionmentioning
confidence: 99%
“…Because of this conflict, salt cedar eradication has been delayed while other control strategies are devised (U.S. Fish and Wildlife Service 1997). Without restoration efforts that assure the re-establishment of native riparian vegetation and restoration of ecosystem function, the removal of invasive salt cedar will result in a loss of nesting habitat for the endangered flycatcher (Zavaleta et al 2001, Dudley and DeLoach 2004, Sogge et al 2008, Dudley and Bean 2012.…”
Section: Discussionmentioning
confidence: 99%
“…Nonnative trees do not break down into pieces as large as native trees, so course woody debris would eventually be absent from the forest floor. Loss of habitat for imperiled riparian species including the southwestern willow flycatcher could occur in response to loss of Goodding's willow and boxelder, though additional research is needed to determine if they will successfully use other woody species as habitat throughout their range (Sogge et al, 2008).…”
Section: Potential Response To Future Changesmentioning
confidence: 99%
“…and the desert cottontail (Sylvilagus audubonii); however, mammal numbers are generally lower in saltcedar than in other vegetation types (EngelWilson and Ohmart 1978). Sogge et al (2008) reported that as many as 49 bird species use saltcedar for breeding habitat in North America. Brown and Trosset (1989) reported that the black chinned hummingbird (Archilochus alexandri Bourcier and Mulsant) nested only in saltcedar in the Grand Canyon, Colorado, because its native habitats were no longer present.…”
Section: Description and Account Of Variationmentioning
confidence: 99%